2022
DOI: 10.2340/actadv.v101.1013
|View full text |Cite
|
Sign up to set email alerts
|

Overall Impairment of Quality of Life in Japanese Patients with Hidradenitis Suppurativa: Comparison with National Standard

Abstract: is missing (Short communication)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…12 and 52 weeks were substantially lower in this study than in the HARMONY study. Health-related QOL is considerably affected by bodily pain, 8 therefore the greater reduction in skin pain observed in this study compared with that observed in the HARMONY study 15 (NRS 1.7 vs. 2.69 at 52 weeks) may have contributed to the difference observed in DLQI scores. Furthermore, given that the baseline DLQI score in this study was similar to that reported by a recent Japanese multicenter questionnaire-based study (8.5 vs. 9.9), 8 the difference in DLQI scores between the current study and the HARMONY study may also be due to the difference in ethnicity (Japanese vs. White).…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…12 and 52 weeks were substantially lower in this study than in the HARMONY study. Health-related QOL is considerably affected by bodily pain, 8 therefore the greater reduction in skin pain observed in this study compared with that observed in the HARMONY study 15 (NRS 1.7 vs. 2.69 at 52 weeks) may have contributed to the difference observed in DLQI scores. Furthermore, given that the baseline DLQI score in this study was similar to that reported by a recent Japanese multicenter questionnaire-based study (8.5 vs. 9.9), 8 the difference in DLQI scores between the current study and the HARMONY study may also be due to the difference in ethnicity (Japanese vs. White).…”
Section: Discussioncontrasting
confidence: 49%
“…This is similar to the results observed in the HARMONY study, 15 which reported an approximately 50% reduction in DLQI from baseline (16.9) to 52 weeks (8.6), although the mean DLQI scores at baseline and at 12 and 52 weeks were substantially lower in this study than in the HARMONY study. Health‐related QOL is considerably affected by bodily pain, 8 therefore the greater reduction in skin pain observed in this study compared with that observed in the HARMONY study 15 (NRS 1.7 vs. 2.69 at 52 weeks) may have contributed to the difference observed in DLQI scores. Furthermore, given that the baseline DLQI score in this study was similar to that reported by a recent Japanese multicenter questionnaire‐based study (8.5 vs. 9.9), 8 the difference in DLQI scores between the current study and the HARMONY study may also be due to the difference in ethnicity (Japanese vs. White).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…A Japanese questionnaire based study similarly found positive correlation between disease severity (PGA, modified Sartorius score, and Hurley stage) and DLQI. 19 No correlation was reported between disease severity and the components of social functioning, role-emotional or mental health of the Short Form-36 health survey version 2 QoL scale was performed in this study.…”
Section: Discussionmentioning
confidence: 72%